2006
DOI: 10.1177/0095798406290467
|View full text |Cite
|
Sign up to set email alerts
|

Lay Theories of Suicide: An Examination of Culturally Relevant Suicide Beliefs and Attributions among African Americans and European Americans

Abstract: The purpose of this study was to examine African Americans' lay beliefs and attributions toward suicide. The Attitudes Toward Suicide Scale, Life Ownership Orientation Questionnaire, Stigma Questionnaire, and Suicide Ideation Questionnaire were administered to 251 undergraduate college students. Beliefs about stigma associated with suicide were comparable across ethnic groups. However, African American college students were significantly less likely than European American college students were to attribute sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 39 publications
1
41
1
Order By: Relevance
“…Consistent with prior research, psychiatric disorders (Cattell, 2000;Cohen et al, 2008;Conwell, 2009;Crocker et al, 2006), including drug use and dependence diagnosis (Slap, Vorters, Chaudhuri, & Centor, 1989) and comorbid psychiatric disorders (Ialongo et al, 2002;Shaffer et al, 1996), were significant predictors of attempted suicide among older Black Americans. Our analyses showed that Blacks with any psychiatric disorder were 4 times more likely to attempt suicide, even when controlling for known protective factors such as religiosity (Chatters, Taylor, Lincoln, Nguyen, & Joe, 2011) and region (Walker, Lester, & Joe, 2006). Unlike previous research on older adults' suicidal behavior, affective disorders were not significant predictors among NSAL respondents.…”
contrasting
confidence: 91%
“…Consistent with prior research, psychiatric disorders (Cattell, 2000;Cohen et al, 2008;Conwell, 2009;Crocker et al, 2006), including drug use and dependence diagnosis (Slap, Vorters, Chaudhuri, & Centor, 1989) and comorbid psychiatric disorders (Ialongo et al, 2002;Shaffer et al, 1996), were significant predictors of attempted suicide among older Black Americans. Our analyses showed that Blacks with any psychiatric disorder were 4 times more likely to attempt suicide, even when controlling for known protective factors such as religiosity (Chatters, Taylor, Lincoln, Nguyen, & Joe, 2011) and region (Walker, Lester, & Joe, 2006). Unlike previous research on older adults' suicidal behavior, affective disorders were not significant predictors among NSAL respondents.…”
contrasting
confidence: 91%
“…For instance, young Black s may have different cultural beliefs and disclose suicidality less readily than Caucasians and therefore may endorse features indicative of suicidality in a unique fashion ( Morrison & Downey, 2000 ;Poussaint & Alexander, 2000 ;Walker & Flowers, 2011 ;Walker, Lester, & Joe, 2006 ). Research indicates that there is stigma related to disclosing thoughts of ending one ' s own life , which has been attributed to religiosity/moral objections and belief in coping/hardiness of the Black community ( Morrison & Downey, 2000 ;Poussaint & Alexander, 2000 ;Walker et al, 2006 ). This might manifest with a decreased endorsement of feeling sad/hopeless, thinking about and/or planning suicide yet endorsing suicide attempts.…”
Section: Tobacco Use and Suicidalitymentioning
confidence: 99%
“…1998). After exploring lay beliefs held among African‐Americans that could serve as a buffer against suicide, Walker et al. (2006) reported several interesting findings.…”
Section: Protective Factors Influencing African‐american Women and Sumentioning
confidence: 99%